1999
DOI: 10.1038/sj.bjc.6690604
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane cofactor protein (MCP, CD46) in human liver diseases

Abstract: Summary Membrane cofactor protein (MCP, CD46) is one of the complement regulatory proteins, and is widely distributed in human organs and protects cells from complement-mediated cytotoxicity. We analysed the distribution and the intensities of MCP in liver diseases and evaluated the role of MCP during hepatocarcinogenesis. Western blot analysis revealed that relative densities (density of the sample/density of the standard sample) of MCP in 27 HCC, 18 liver cirrhosis, nine chronic hepatitis and 12 normal liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…The results of these studies confirmed overexpression of CD46 in HCC tumor tissue compared to nonmalignant hepatic tissue. Our data are in concordance with an earlier study by Kinugasa et al, 43 which compared CD46 expression in normal human hepatic tissue, HCC, cirrhosis, and chronic hepatitis samples. Their results showed relative CD46 densities of 0.11 ϩ 0.1 in normal hepatic tissue, 0.63 ϩ 0.23 in HCC, 0.21 ϩ 0.07 in cirrhosis, and 0.25 ϩ 0.1 in chronic hepatitis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of these studies confirmed overexpression of CD46 in HCC tumor tissue compared to nonmalignant hepatic tissue. Our data are in concordance with an earlier study by Kinugasa et al, 43 which compared CD46 expression in normal human hepatic tissue, HCC, cirrhosis, and chronic hepatitis samples. Their results showed relative CD46 densities of 0.11 ϩ 0.1 in normal hepatic tissue, 0.63 ϩ 0.23 in HCC, 0.21 ϩ 0.07 in cirrhosis, and 0.25 ϩ 0.1 in chronic hepatitis.…”
Section: Discussionsupporting
confidence: 93%
“…57,58 The observation that CD46 expression is increased in cirrhosis, though still 3 times lower than in HCC, indicates clinical phase I toxicity studies are necessary. 43,52 In addition, our previous data showed that intraperitoneal treatment of Ifnar ™ -CD46Ge transgenic mice with MV-GFP did not result in significant transgene expression, despite the presence of MV-Edm RNA in liver tissue. 59 These data support the safety and suggest the tumor selectivity of MV-Edm.…”
Section: Discussionmentioning
confidence: 93%
“…Like most mCRPs, it is expressed on various tumors including head and neck squamous cell carcinoma (HNSCC) (102), hematological malignancies (93,103), breast, prostate (104), ovarian (105,106), glioma (107), liver (108), renal (25) and cervical cancer (109) among others. Together with CD55, downregulation of CD46 with siRNA resulted in increased CDC in a number of cell lines (99,110).…”
Section: Crpsmentioning
confidence: 99%
“…Recently, relative resistance of malignant tumor cells to infection with Ad5-based vectors has been connected to downregulation of CAR and/or integrin expression on target cell membranes. [4][5][6][7] Group B Ad serotypes (Ad3, 7,11,14,16,21,34,35,50) use a receptor other than CAR. We and others recently identified CD46 as a cellular receptor that is used by most B-group Ads.…”
Section: Introductionmentioning
confidence: 99%